Phenolic Content and Antioxidant Activity of Colocasia esculenta in Commercial Herbal Products - Nugroho, Gumilar Adhi; Desmiaty, Yesi; Sumiyati, Yati; Suherman, Sandra Loretta; Lim, Helsa (Sciences of Phytochemistry, 2025)
Taro (Colocasia esculenta L.) is a plant with a long history of use in traditional medicine in several countries worldwide. The corm of taro and two commercial products were analysed due to total phenolic, flavonoid, luteolin, and antioxidant properties. Taro corm was extracted with water and analysed for phytochemical screening, total flavonoids, total phenolic, luteolin, and antioxidant properties. The phytochemical screening of taro showed that it contains secondary metabolites of flavonoids, tannins, saponins, triterpenoids, and quinones. The results of the determination of total flavonoid content of taro extract, Product 1, and Product 2 capsule obtained 19.34 ± 0.26 mg QE/g extract, 18.58 ± 0.18 mg QE/g extract, and 16.29 ± 0.23 mg QE/g extract. The results of determining the total phenolic content of taro, Product 1, and Product 2 capsules obtained 39.75 ± 0.95 mg GAE/g extract, 38.46 ± 0.46 mg GAE/g extract, and 35.91 mg GAE/g extract. ± 0.82 mg GAE/g extract. The results of the determination of luteolin from taro, Product 1, and Product 2 capsules obtained 0.83 ± 0.05 %, 0.39 ± 0.04 %, and 0.18 ± 0.08 %. The results of the antioxidant activity test obtained IC50 of vitamin C of 4.6780 ± 0.0319 ppm, corm dry extract and ginger rhizome 141.2383 ± 3.4995 ppm and 97.6685 ± 7.8760 ppm, respectively, and capsule products 2; 126.0724 ± 1.3672 ppm. The water extract of corm and available products containing CE extract have met the quality standard parameters required for non-specific parameters, luteolin content, and antioxidant properties.